Campus Canopy, 1944-10-31 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1944)
Sock and Buskin Club Announces Play and Cast -- In Spirit of cooperation Make Little Things Count -- Seven Attend GHEA in Atlanta Last Week-end -- Artist Series Com. Announces Bookings For Year -- Metropolitan Stars Gives Concert Friday Night -- Campus Poll Reveals Many Real Little sisters Here -- Final Plans For Senior Carnival Bring Surprises
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals